Developing quality criteria for Participatory Health Research: An agenda for action - Jane Springett; Michael T. Wright; Brenda Roche (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2011)
Participatory Health Research (PHR) builds on a long and diverse history drawn from a range of disciplines, each of which have informed and developed their own understanding of what participatory research practice is. However, just as with qualitative methods ten to fifteen years ago, there is an increasing interest in setting out the fundamental principles that should drive the assessment of quality within PHR. While those using participatory research methods in health have often called for a review of quality criteria, to date there has not been anything published that undertakes the same substantive systematic attempt as found in qualitative research and evaluation. This paper starts the process of agenda setting on quality criteria by describing some key notions/issues that are core to PHR and relevant for developing steps for action, drawing together some key literature. The paper arose from the work of the International Collaboration on Participatory Health Research (ICHPR). Through consolidating existing knowledge and reaching agreement on common terminology and principles, the ICHPR seeks to strengthen the role of PHR in intervention design and decision-making on health issues. This includes developing guidelines for conducting and evaluating PHR, describing which forms of theory and evidence are produced by this approach, and finding a means for conducting systematic reviews of the PHR literature in order to contribute to the body of interna-tional knowledge on community health. – – Die Partizipative Gesundheitsforschung (PG) entstand über einen längeren Zeitraum aus einer Vielfalt an Disziplinen, die zum Teil unterschiedliche Auffassungen von Partizipativer Forschung vertreten. Wie bei den qualitativen Forschungsansätzen vor ca. fünfzehn Jahren befassen sich immer mehr partizipativ forschende Wissenschaftler/innen mit der Ausformulierung von Gütekriterien für diese Form von Forschung. Mehrere Autor/inn/en haben einen Bedarf an einer systematischen Betrachtung der bereits formulierten Gütekriterien festgestellt, jedoch gibt es bis heute noch keinen Beitrag, der mit den Abhandlungen zu den Gütekriterien der qualitativen Forschung vergleichbar wäre. Dieses Manuskript stellt einen Versuch dar, aufgrund einschlägiger Literatur einen konzeptuellen Rahmen für die Diskussion über Gütekriterien auf dem Gebiet der PG aufzustellen. Es ist ein Ergebnis der Arbeit der International Collaboration on Participatory Health Research (ICHPR). Die ICHPR hat als Ziel, internationale Erfahrungen und Wissensbestände zum Thema Partizipative Gesundheitsforschung zusammenzuführen und einen Konsens über Definitionen und Kernprinzipien zu erreichen, um eine breitere Anerkennung und Anwendung dieses relativ neuen Forschungsansatzes zu fördern. Dies beinhaltet u. a. zu klären, welche Formen von Theorie und Evidenz durch PG generiert werden und nach welcher Vorgehensweise die Ergebnisse aus lokal situierten, partizipativ angelegten Studien systematisch zusammengetragen werden können, um einen Betrag zur internationalen Debatte über die sozialen Determinanten von Gesundheit zu leisten.
Keywords: 300